SPATIAL VARIATION OF THE PLANKTON COMMUNITY OVER A SHORT-TERM SURVEY AT A TROPICAL HYPEREUTROPHIC ESTUARY - Guenther, Mariana; Jeanne Royer, Sarah; Campos, Danniely de Oliveira; Leitão, Sigrid Neumann (Arquivos de Ciências do Mar, 2015)
Composition, abundance, diversity and evenness of phytoplankton (micro: > 20 μm) and zooplankton (micro: 20- 200 μm and meso: > 200 μm) were assessed at three different points of Recife Harbor (NE Brazil), a hypereutrophic estuary, during the wet season. Its spatial structure was clearly heterogeneous, being the phytoplankton more abundant and less diverse at the inner portion, due to a Thalassiosira bloom. Micro and mesozooplankton were more abundant at the intermediate and outer estuary. Ciliates (e.g., Codonella spp.) dominated the microzooplankton at the inner system while Gastropoda larvae prevailed at the outer section. In the mesozooplankton community, cyclopoid copepods (e.g., Oithona hebes) were more abundant at the inner section while calanoids (e.g., Parvocalanus crassirostris) prevailed at the outer system. Tidal oscillation effects on plankton dynamics were more important near the estuary’s mouth. These results suggest that the variations in abiotic factors may not be enough to explain the effects of eutrophication on such hydrological dynamic systems and raise some hypotheses about the more likely biotic regulation of those communities such as competition and predation, to be evaluated on a long-term basis